Integrated Web-Based Learning Approach and The Students’Academic Achievement - Meliza P. Alo; Domingo V. Origines JR. (Proceeding of International Conference on Science, Health, And Technology, 2021)
The main objective of this study was to determine the effectiveness of integrated web-based learning approach in enhancing the academic performance in Science of Grade 7 students. The researcher used the quasi-experimental research design in to attain the objectives. Specifically, this study used the pretest-posttest non-equivalent control design in assigning groups and in applying the treatments. The study was conducted from January, 2019 to March 2019 comprising the fourth grading period. A 40-item researcher-made test questionnaire was used to determine the performance of Grade 7 students in both the control and experimental groups before and after the treatment. Data were gathered, collated and analyzed using mean, standard deviation and t-test for independent sample at 5% level of significance. The pretests mean score in the control group was 75.00 and the experimental group was 76.20, both at the developing level. The posttest mean score rating in the control group was 78.20 and remained at the developing level, while the experimental group was 85.10, increased to approaching proficient level. The mean gain rating of the Grade 7 science students in experimental group was 13.97 higher compared to the mean rating of control group that is 9.23 not exposed to integrated web-based learning approach. No significant difference on the pretest mean score ratings between Grade 7 students who were exposed and not exposed to the integrated web-based learning approach while a significant difference on the posttest mean score were noted. Furthermore, there was a significant difference on the mean gain score ratings of Grade 7 students in Science utilizing the traditional method and integrated web-based learning approach. Integrated web-based learning approach was found effective in improving the academic achievement of Grade 7 students in Science.